THE PROPORTION OF X AND Y SPERM, VIABILITY AND MOTILITY OF RAM SPERMATOZOA AFTER SEPARATED WITH WHITE EGG ALBUMIN - Moh Takdir; Ismaya ismaya; Sigit Bintara (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
ABSTRACT The aim of this research was to determine the proportion, viability and motility of X and Y ram spermatozoa separated with egg white albumin. Sperm samples derived from Garut ram, which was collected by using an artificial vagina. Observations were made on spermatozoa fraction above and below each medium fraction treatment. There are treatment egg white albumin as separation medium, each medium consisting of fractions top and bottom fraction with different concentration: 1) P0 = sperma before separation (control); 2) P1 = 10% above fraction + 30% lower fraction; P2 = 25% + 45%; P3 = 25% + 75%. Data proportion of X and Y, viability and motility were analyzed statistically by Completely Randomized Design patern in the direction followed by Duncan’s Multiple Range Test for data with a real difference. Separation with egg white albumin affect significantly increased the proportion of spermatozoa X and Y (P≤0.05), but tends to decrease the viability and motility of spermatozoa.The proportion of spermatozoa X and Y was highest in treatment P3,76.76% of spermatozoa X (fraction above 25%) and 79.81% spermatozoa Y (75% lower fraction), with an average viability obtained respectively 68,9% (fraction above) and 59,7% (bottom fraction), motility 77,5% (fraction above) dan 84,0% (bottom fraction). It was concluded that the egg white albumin is very effective in changing the proportions of X and Y ram sperm with the quality of spermatozoa after separation feasible for applications insemination or processed into frozen semen. (Keywords: Garut ram, White egg albumin, Spermatozoa X and Y)